(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
The climatic conditions of Uzbekistan are favorable for the cultivation of crops adapted to the subtropical climate. These include figs. These tree-shrubs have been planted since ancient times and have become a branch of horticulture for the countries of Central Asia, including the people of Uzbekistan.